Elastic Buffering Layer on CuS Enabling High-Rate and Long-Life Sodium-Ion Storage - Xiao, Yuanhua; Yue, Feng; Wen, Ziqing; Shen, Ya; Su, Dangcheng; Guo, Huazhang; Rui, Xianhong; Zhou, Liming; Fang, Shaoming; Yu, Yan (Nano-Micro Letters, 2022)
The latest view suggests the inactive core, surface pulverization, and polysulfide shuttling effect of metal sulfides are responsible for their low capacity and poor cycling performance in sodium-ion batteries (SIBs). Whereas overcoming the above problems based on conventional nanoengineering is not efficient enough. In this work, erythrocyte-like CuS microspheres with an elastic buffering layer of ultrathin polyaniline (PANI) were synthesized through one-step self-assembly growth, followed by in situ polymerization of aniline. When CuS@PANI is used as anode electrode in SIBs, it delivers high capacity, ultrahigh rate capability (500 mAh g−1 at 0.1 A g−1, and 214.5 mAh g−1 at 40 A g−1), and superior cycling life of over 7500 cycles at 20 A g−1. A series of in/ex situ characterization techniques were applied to investigate the structural evolution and sodium-ion storage mechanism. The PANI swollen with electrolyte can stabilize solid electrolyte interface layer, benefit the ion transport/charge transfer at the PANI/electrolyte interface, and restrain the size growth of Cu particles in confined space. Moreover, finite element analyses and density functional simulations confirm that the PANI film effectively buffers the volume expansion, suppresses the surface pulverization, and traps the polysulfide. Highlights: 1 Erythrocyte-like CuS microspheres were encapsulated in ultrathin polyaniline (PANI) layer coating. 2 PANI swollen by electrolytes stabilizes solid electrolyte interface layer and benefits the ion transport and charge transfer at the PANI/electrolyte interface. 3 Multi-functional PANI coating ensures an outstanding comprehensive performance for sodium-ion storage.